Rehabilitasi dan Rekonstruksi Bangunan Gereja Masehi Injili Timor Pasca Bencana Seroja di Kabupaten Sabu Raijua - Budhi Benyamin Lily; Apridus Kefas Lapenangga; Stella Malelak (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2023)
Sabu Raijua Regency consists of Sabu Island and Raijua Island which are in East Nusa Tenggara. This area was also affected by the Seroja disaster that occurred in April 2021. Many buildings collapsed, including several church buildings which spread across the island due to the strong winds. The method used in this study is descriptive qualitative in an inductive approach by explaining the pattern of damage and repair plans for church buildings due to the Seroja tropical cyclone disaster in the Sabu Raijua district and formulating guidelines for rehabilitation and reconstruction. The purpose of this research is to formulate guidelines for the rehabilitation and reconstruction of church buildings after the Seroja tropical cyclone disaster so that people in carrying out development activities no longer rely on makeshift understanding and technology but need to consider technical requirements. The results of this research are in the form of recommendations set forth in this guideline for the rehabilitation and reconstruction of church buildings on the island of Sabu.